168: Failure of Free, Public Vitamin D Supplementation Program for Quebec Infants – Temporal Trends and Significant Predictors. Issue 6 (1st June 2014) - Fatani, T; Millette, M; Sheehy, O; Berard, A; Weiler, H; Sharma, A; Rodd, C
Abstract: BACKGROUND: To prevent deficiency several agencies including the CPS recommend 400 IU/d of vitamin D in infancy. For nearly 20 years, Quebec has offered a program of free supplements through its public medication insurance plan (RAMQ). Other jurisdictions have implemented programs to enhance vitamin D supplementation. OBJECTIVES: Our study sought to evaluate the uptake of vitamin D via this prescription program in both term and preterm infants and determine the incidence of nutritional rickets over this time. DESIGN/METHODS: This was a retrospective cohort study of infant; the data are derived from the province of Quebec, Canada. All healthy infants born between 1998 and 2008 and covered by RAMQ drug plan were included. Data were extracted from the Quebec Pregnancy Cohort built by the linkage of three databases: RAMQ medical and prescription databases (diagnoses, medications, SES), MedEcho (hospitalizations), and ISQ (birthweight, SES). Predictors of program participation were identified through logistic regression (GEE). RESULTS: A total of 123, 018 term infants were eligible for RAMQ and the mean annual prevalence of supplemental vitamin D exposure was 17.9±5.6%. The median age for obtaining the first bottle was 36 days (range 1 to 370). The majority (51.0%) obtained only one bottle of fifty doses (median 1, range 1 to 20). 8812 preterm infants were similarly eligible; vitamin D exposure was 34% in early (23 to 33 weeks) and 17% in late preterm infants. The median age was 49 days and the median number of bottles was two (range one to 15). For all infants, mothers of higher SES, those who lived as a couple, older mothers, or a prescription by a pediatrician significantly increased the odds of obtaining vitamin (P<0.05). Additionally, there was a statistically significant decline in program participation over time (OR 0.89 per year, 95% CI 0.88 to 0.90). The overall incidence of nutritional rickets was 23.9 cases per 100, 000 live births with an annual increase of 1.12 cases per year (Poisson regression, 95% CI 1.01 to 1.24). CONCLUSIONS: Without specific educational measures, a free prescription program for vitamin D failed to encourage participation or long-term adherence. Moreover, participation decreased with time and coincided with an increase in the incidence of rickets. Higher SES and care by a pediatrician increased odds for participation. New strategies targeting these variables and providing educational support for healthcare workers and the general community may need to be developed to increase vitamin D supplementation rates.